Empreendimento solidário de beneficiamento de resíduos recicláveis (upcycling) do Titanzinho, Serviluz, Fortaleza-CE - Mesquita, Beatriz Chagas de (2013)
We live a capitalist experience of socioeconomic organization that behind the veil of economic liberalism, representative democracy and consumption, offers the Market the power to rule society, among environmental destruction, politics dismissal and social deterioration. It is common to experiment overexploitation of natural resources and workers, production inefficiency, waste accumulation, elitists privileges and the authoritarianism of an exclusionary State. We need to build connections between development, economy, society and the environment. For that purpose, an upcycling enterprise was developed at the marginalized community of Titanzinho, Serviluz Fortaleza-CE). Upcycling is the creation of new products with good quality and socio-environmental value from used, thrown-out elements that used to be treated as trash and waste. According to the principles of solidarity economy and creative cultural economy, focused on the welfare of people at work, we fight poverty through employment and income opportunities, the development of technical and organizational skills and critical education, encouraging the engagement of mothers, a group of social vulnerability. It is an interventional, observational and descriptive research. Strategic planning was necessary to start the new economic activity. Action research, participant observation and social representation were chosen as investigative techniques to assist the enterprise management, to understand reality, and the meaning of the public attended actions and the project’s influences on their lives. The registration of events and everyday perceptions on documents revealed the indicators to measure the results. Economic growth, ecological balance and social justice are combined by the upcycling entrepreneurial activity, offering prospects for personal fulfillment and collective well-being, contributing to cultural values and practices towards sustainable development. The benefits are difficult to be measured in financial terms.